PENGARUH KOMITMEN ORGANISASI, GAYA KEPEMIMPINAN DAN PELATIHAN PROFESI PADA KINERJA AUDITOR - Regina Amandani, Ni Made; Wirakusuma, Made Gede (E-Jurnal Akuntansi, 2017)
This study aimed to determine the effect of organizational commitment, leadership style and professional training on the performance of auditors of public accounting firms in the province of Bali. The sampling method used is purposive sampling method. Data collection is done by using questionnaire. The samples used were 46 respondents. Data analysis technique used is multiple linear regression analysis. The results indicate that organizational commitment  has positive effect on the performance of auditors shows that the higher the attitude of the commitment of an auditor the more it will affect its performance. Leadership style has positive effect on the performance of auditors which shows that the better way to lead the leaders will increasingly affect the performance of auditors. Professional training has a positive effect on the performance of auditors which shows that the more often the training given to the auditor, the auditor's performance will tend to increase.
Keywords: organizational commitment; leadership style; professional training; performance auditor